Corneal Higher-Order Aberrations after Descemet's Membrane Endothelial Keratoplasty - Rudolph, Michael; Laaser, Kathrin; Bachmann, Bjoern O.; Cursiefen, Claus; Epstein, Daniel; Kruse, Friedrich (Ophthalmology, 2012)
We compared corneal higher-order aberrations (HOAs) in eyes after Descemet's membrane endothelial keratoplasty (DMEK), Descemet's stripping automated endothelial keratoplasty (DSAEK), and penetrating keratoplasty (PK), and in a control group that had not undergone surgery.Retrospective analysis of clinical data.Thirty eyes of 30 patients who had undergone standard DMEK, 20 eyes of 20 patients after DSAEK, 20 eyes of 20 patients after PK, and 20 eyes of 20 controls were analyzed.In addition to standard postoperative examinations, each participant was analyzed with the Pentacam high-resolution rotating Scheimpflug imaging system (Pentacam HR, Oculus, Wetzlar, Germany). Data were compared between groups.Visual acuity and HOAs.The mean follow-up was 6.5±1.2 months after DMEK, 22.6±11.8 months after DSAEK, and 103.1±74.2 months after PK. There were no statistically significant differences for the anterior 4.0-mm zones between the DMEK group and the controls or between the DMEK and DSAEK groups. The DMEK procedure compared with PK showed statistically significant differences in all terms for the 4.0-mm zones. All combined Zernike terms for mean posterior aberrations of the central 4.0-mm zones showed statistically significant higher aberrations for DMEK compared with controls. The DMEK procedure compared with DSAEK showed statistically significant lower mean values for all combined Zernike terms, except for coma and coma-like terms in the central 4.0-mm zones of the posterior corneal surface. Compared with PK, DMEK showed statistically significant lower mean values for all combined Zernike terms for the central 4.0-mm zones of the posterior corneal surface, except for spherical aberration (SA) and SA-like terms. Best spectacle-corrected visual acuity (BSCVA) after DMEK was statistically significantly better than after DSAEK (P=0.001) and PK (P=0.005). There was no statistically significant difference when BSCVA was compared with controls (P=0.998).Both DSAEK and PK exhibit increased posterior corneal HOAs even years after surgery. Patients receiving DMEK display only slight changes in posterior corneal HOAs.Proprietary or commercial disclosure may be found after the references.
EVALuna2:21073

Frosted branch angiitis : Clinical findings and Spectralis OCT follow-up - Bergua, A.; Galiano, M.; Hohberger, B.; Rudolph, Michael (Ophthalmologe, 2016)
Frosted branch angiitis is a special form of retinal vasculitis, which has only rarely been reported in the literature. Although the majority of cases of frosted branch angiitis are idiopathic, a systematic clinical work-up should be done in order to exclude other causes, such as infectious and autoimmune diseases. The aim of this study was to correlate the clinical findings with the images obtained during follow-up by spectral domain optical coherence tomography (OCT).
EVALuna2:21248

Pattern electroretinograms during the cold pressor test in normals and glaucoma patients - La Mancusa, Antonia; Horn, Folkert; Kremers, Jan; Huchzermeyer, Cord; Rudolph, Michael; Jünemann, Anselm (Investigative Ophthalmology & Visual Science, 2014)
To examine the influence of the cold pressor test (CPT) on steady-state pattern electroretinograms (PERG) in healthy subjects and glaucoma patients.Steady-state PERGs to 7.8 Hz pattern reversal stimuli were recorded in 63 subjects. Fifteen healthy control subjects, 14 patients with ocular hypertension (OHT), and 34 patients with open-angle glaucoma (20 normotensive [NTG] and 14 high tension glaucoma [HTG]) were examined. Steady-state PERG amplitudes and latencies were analyzed at baseline, during cold stimulus using a modified CPT, and during the subsequent recovery phase. Blood pressure and heart rate were simultaneously recorded in 10 normals and 11 glaucoma patients.During the three test conditions (baseline, ice water, and warm water) glaucoma patients (NTG and HTG) showed significantly reduced PERG amplitudes in comparison with control subjects (P < 0.001) and with OHT patients (P < 0.004). Patients with OHT displayed lower PERG amplitudes than control subjects (nonsignificant, with consideration of Bonferroni). Only NTG patients showed a significant effect of the CPT on PERG amplitude (significant decrease during warm water P = 0.02). Latencies shortened significantly during warm-water period after cold stimulus in control subjects (P = 0.05) and in NTG patients (P = 0.02) with a nonsignificant trend of shortened latencies in the OHT (P = 0.06) and HTG groups (P = 0.3). Systolic and diastolic blood pressure increased during cold water (P < 0.001) and decreased during warming-up conditions (P < 0.001).This study shows that a CPT influences the PERG responses particularly in NTG. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21162